Lehren aus den Rentenreformen seit 1972 - Axel Börsch-Supan (Wirtschaftsdienst, 2015)
– Thanks to the reform process between 1992 and 2007, Germany was in a very good position to master demographic change. These reforms were farsighted, they stabilised the public pension system and they significantly increased employment, the foundation of every old age provision. The 'Pension Package 2014', however, is putting this position in jeopardy by focusing on the older generation at the expense of the young, whoich needs more education and better health care, areas in which Germany exhibits only mediocre performance. A farsightedIf a demographicy strategy wants to be farsighted, its core cannot centre onbe reductions in the retirement age and similar expensive steps backwards, but will instead require investments into Germany's youth.
Keywords: H55; J11; J26; 330; Rentenreform; Wirkungsanalyse; Deutschland